Ontologi Pendidikan Islam: Studi Kasus Pengajaran Nilai Islam di Pesantren Baitul Qur’an Wonogiri - Mujiburrohman, Mujiburrohman; Luthfi, Moh (Lembaga Yasin AlSys, 2025)
Pesantren (Islamic boarding schools) are the oldest Islamic educational institutions in Indonesia. Over time, pesantren have been influenced by the development of education and the dynamic needs of society. Some pesantren now offer formal education and other activities aimed at enhancing the economic potential of the surrounding community by establishing pesantren as central hubs. The management and operations of pesantren are always grounded in the philosophy of education. This study aims to describe the educational philosophy at Pondok Pesantren Baitul Qur’an Wonogiri. The research model employed is field study, which involves direct engagement in the field to explore philosophical issues in khalaf pesantren (modern pesantren). The research uses a qualitative method, defined as gathering research data through interviews, observations, and document analysis. Observations were conducted directly at Pondok Pesantren Baitul Qur’an Wonogiri. This study yielded findings related to the ontological foundations of the philosophy of education at Pondok Pesantren Baitul Qur’an Wonogiri.